G61(P) Nusinersen administration – the oncology intrathecal way. (May 2019) - Aung, W; Roe, L; Thompson, S
Abstract : Aims: Following the success of the use of intrathecal Nusinersen in the ENDEAR trial for the treatment of SMA Type 1, eligible patients have had access to this treatment via Biogen's Expanded Access Programme. Our centre has been approved since April 2017 with a total of 9 patients to date, receiving regular treatment. In comparison to others, we have utilised our expert Oncology service and high dependency unit to deliver the intrathecal treatment as a day case procedure (where appropriate). As there is no current standardised administration protocol we wanted to review how other centres were carrying out the procedure in comparison to ours. Method: We present a survey of centres in England who currently provide Nusinersen to assess variation in practice in comparison with our established pathway that has been found to be effective and well tolerated. Results: Majority of the centres used their Neurology or Neuromuscular Services to facilitate treatment with intrathecal procedures done under local anaesthetic as a day case, however some patients did need a general anaesthetic. Depending on centre's level of care, patients were admitted to either specialist wards or high dependency care unit. Conclusion: By utilising the skills of those with many years of intrathecal chemotherapy administration the safety procedures were well established and the procedure is well tolerated with only minimal analgesia.